Appraisal of emotional intelligence skills of university students in terms of different variables - Banu Dikmen Ada; Asude Balaban Dağal (International Journal of Evaluation and Research in Education (IJERE), 2022)
This research investigated whether the emotional intelligence skills of first- and fourth-grade university students differ according to the departments they are enrolled in and other factors. In this research, the 87-item Bar-On Emotional Quotient Inventory was used. In the intrapersonal, interpersonal, and adaptability sub-dimension a significant difference was found in favor of those who attended Mathematics and Pre-school Education departments. When the ‘interpersonal’ and ‘adaptability’ subscales were examined, the results were observed to be in favor of Environmental Engineering Department. When the independent group t-test results were examined with respect to gender variable, the significance of ‘interpersonal’ and ‘adaptability’ subscales was in favor of male students.